Analisis Perbandingan Quality of Service Modul FXS dengan Internet Telephony Gateway - Fathony Ilham Eka Putra (Politeknik Negeri Malang, 2020)
Nowadays the exchange of information is easier to obtain, also communication process is faster and not hindered by regional factors. This process is supported by telecommunications devices, such as telephones. The use of telephones in agency generally uses PBX system because it has advantages in cost, flexibility, and communication security. With the development of the era, the technology of PBX devices must be updated, but there is a solution besides updating the device, which is to add modules or devices while still using the existing PBX. This research discuss the analysis regarding the comparison of service quality of the Internet Telephony Gateway with the FXS module. The system uses the network as a medium for exchanging communication data, so all communication devices used must be connected to the local network. Communication between devices can occur when each communication device is registered on the PBX server. Testing the quality service is influenced by amount of jitter, packet loss, and throughput. From the test results, it can be concluded that the number of active users simultaneously affects the value of jitter, packet loss, and throughput. When 8 ports of the FXS module are used simultaneously, the average jitter value reaches 27,625 ms, the packet loss value is 156,875%, and the throughput is 66,625 kb/s. Meanwhile, the TA1600 was able to serve 16 users with an average jitter value of 57,875 ms, packet loss reaching 227.31%, and a throughput of 26.31 kb/s. These results were obtained through the Zoiper application statistical data.